Analisis Korelasi Kanonikal Komponen Aktiva - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
ABSTRACT The independence of asset and liability composition is obvious in Modigliani and Miller 's capital structure proposition. While, independence of investing and financing decisions is a very useful assumption to simples corporate financial decisions, the actual balance sheets of corporations do not reveal independence between the two sides of the balance sheet. The purposes of this paper are to empirically identi& relationship between the structures of left side and right side of balance sheet and to explain the nature of these relationships by using canonical correlation analysis. Canonical correlation analysis shows that firms match the maturity structure of their assets and liabilities, short-term (long-term) assets tend to be financed with short-term (long-term) liabilities, accounts receivable are used as collateral for short-term loan, and fixed assets are use as collateral for long-term loan.